Carnosine Content in Skeletal Muscle Is Dependent on Vitamin B6 Status in Rats - Suidasari, Sofya; Stautemas, Jan; Uragami, Shinji; Yanaka, Noriyuki; Derave, Wim; Kato, Norihisa (Frontiers in Nutrition, 2016)
Carnosine, a histidine-containing dipeptide, is well known to be associated with skeletal muscle performance. However, there is limited information on the effect of dietary micronutrients on muscle carnosine level. Pyridoxal 5′-phosphate (PLP), the active form of vitamin B6, is involved in amino acid metabolisms in the body as a co-factor. We hypothesized that enzymes involved in β-alanine biosynthesis, the rate-limiting precursor of carnosine, may also be PLP-dependent. Thus, we examined the effects of dietary vitamin B6 on the muscle carnosine content of rats. Male and female rats were fed a diet containing 1, 7, or 35 mg pyridoxine HCl/kg for 6 weeks. Carnosine in skeletal muscles was quantified by ultra-performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS). In the gastrocnemius muscle of male rats, carnosine concentration was significantly higher in the 7 and 35 mg groups (+70% and +61%, respectively) than in the 1 mg pyridoxine HCl/kg group, whereas that in the soleus muscle of male rats was significantly higher only in the 7 mg group (+43%) than in the 1 mg pyridoxine HCl/kg group (P<0.05). In both muscles of female rats, carnosine concentration was significantly higher in the 7 and 35 mg groups (+32% ~ +226%) than in the 1 mg pyridoxine HCl/kg group (P<0.05). We also found that compared to the 1 mg group, β-alanine concentrations in the 7 and 35 mg groups were markedly elevated in gastrocnemius muscles of male (+153% and +148%, respectively, P<0.05) and female (+381% and +437%, respectively, P<0.05) rats. Noteworthy, the concentrations of ornithine in the 7 and 35 mg groups were decreased in gastrocnemius muscles of male rats (−46% and −54%, respectively, P<0.05), which strongly inversely correlated with β-alanine concentration (r=−0.84, P<0.01). In humans, 19% lower muscle carnosine content was found in soleus muscle of women of the lower plasma PLP tertile, but this was not observed in gastrocnemius muscle or in men. We conclude that adequate dietary vitamin B6 is essential for maintaining carnosine in skeletal muscles of rats. Significantly lower soleus carnosine content among women close to PLP deficiency suggests a similar phenomenon exist in the humans.